Book review: Giulia Battaglia, Documentary Film in India: An Anthropological History. (June 2019) - Matzner, Deborah
Giulia Battaglia, Documentary Film in India: An Anthropological History . London and New York, NY: Routledge, 2018, 248 pp., 82.25. ISBN: 978–1–13855173–2.